The association between self-reported grocery store access, fruit and vegetable intake, sugar-sweetened beverage consumption, and obesity in a racially diverse, low-income population - Lauren Nichol Gase; Amelia Rose DeFosset; Lisa V Smith; Tony eKuo; Tony eKuo; Tony eKuo (Frontiers Media S.A., 2014)
This study sought to examine the relationship between self-reported time and distance to the nearest retail grocery store, healthy and unhealthy food consumption, and objectively measured body mass index. We conducted a survey with 1,503 racially diverse, low-income residents at five public health centers in Los Angeles County. Most participants reported shopping at a supermarket (86.7%) and driving (59.9%) to their usual source for groceries. Over half reported living less than a mile from (58.9%) and traveling five minutes or less to reach (50.3%) the nearest grocery store. In the multivariable regression models, neither self-reported distance nor time to the nearest grocery store was consistently associated with fruit and vegetable intake, sugar-sweetened beverage consumption, or body mass index. Results suggest the need to consider access and quality as well as urban planning and transportation, when examining the relationship between the retail food environment and health outcomes.